Implementation of School-Based Environmental Management to Create a Culture of Environmental Care in Elementary Schools - Fatkhia Nur Azizah; Sofia Nanda Saputri; Dina Puspita Anggraini; Sri Suwartini (International journal of technology and education research, 2026)
Rapid global development and technological advancements have led to an increase in human needs and caused a number of environmental problems. This situation is exacerbated by humans irresponsible use of natural resources. Therefore, a systematic approach is needed to instill environmental awareness from an early age, particularly through education at the elementary school level. This study aims to analyze the implementation of environmental management in schools to foster an environmentally conscious character among students. The methodology employed is a literature review using document analysis techniques from various references. The results indicate that environmental management in schools can be implemented through integrated steps of planning, organizing, executing, and monitoring, embedded within policies, curricula, participatory activities, and the management of environmentally friendly facilities. This implementation can shape students' environmentally conscious character through the cultivation of attitudes, knowledge, and skills. In other words, school-based environmental management serves as an efficient strategy for building green schools and enhancing the quality of sustainable education.